On Frequency and Time Characteristics of S-Bursts with Linear Drift of Jovian DCM Radio Emission. I. Formation of the Burst - Boev, A. G.; Scherbinina, T. E. (Видавничий дім «Академперіодика», 2013)
On Frequency and Time Characteristics of S-Bursts with Linear Drift of Jovian DCM Radio Emission. I. Formation of the Burst